A CRITICAL STUDY ON IMPACT OF POLITICS IN INDIAN EDUCATIONAL SYSTEM - RAVALI, V.; VEZHAVENTHAN, D. (International Journal of Psychosocial Rehabilitation, 2020)
The present study was conducted in certain regions of Tamilnadu in order to analyse the dispute resolution in India. The main aim of the research is to create awareness about the impact of politics in Indian educational system. In this regard, the study has made an attempt to examine the influence of politics in Indian educational system. Towards the end of the study, it is revealed that there is a significant change in the impact of politics in implementation of laws in the education system. This research paper will discuss in detail about the people’s awareness in Tamilnadu about the impact of politics in Indian educational system.. The survey which was conducted among the general public also stated that there is a significant change in the impact of politics in implementation of laws in the education system. The results reveal that the general public mostly are not aware of the impact of politics in Indian educational system. This paper makes an attempt to create an awareness among the general public about the impact of politics in Indian educational system.